Beginning Azure functions : building scalable and serverless apps - Sawhney, Rahul; Chanumolu, Kalyan (Apress, 2023)
Start creating highly scalable apps and monitoring your Azure functions in production using Azure Functions 4.0. This book thoroughly explains durable functions for statefulness, covering the basics all the way through how to create bindings in durable functions. It's a deep dive into the Azure Functions serverless API and will guide you through the process of converting monolithic applications to use Azure Functions. This updated edition is revised to cover changes to Azure Portal and delves into Azure Functions runtime versions, the Isolated Process model, and offers a comparison of Azure Functions and Azure Logic Apps. You'll also learn how to register binding extensions and gain an introduction to Azure Functions binding expression patterns, along with best practices for using Azure Functions. Beginning Azure Functions will provide you with the foundational knowledge to work with Azure Functions and teach you practical skills, such as how to create Azure Functions using different triggers and bindings. You'll also see how to monitor your Azure Functions in production with live monitoring, and how to perform remote debugging and how to secure your functions. Upon completing this book, you'll understand Azure Functions and how to create them using the Azure portal and Visual Studio.